DUA MEDIA, DUA CERITA: KENAPA CNBC INDONESIA DAN BLOOMBERG TECHNOZ BERBEDA SAAT MELIPUT IHSG AMBRUK 2026 - Naufal Ilham Ramadhan; Khusnul Nuril; Fachri Juliansyah; Syaida Salwa; Devia Eka; Zainul Mukarobin; Ahmad Hakimudin Resa; Dian Setyawan; Tegar Bimantara; Malik Ibrahim (Nusantara Hasana Journal, 2026)
This study aims to uncover the differences in media framing of the 2026 Indonesian Composite Stock Price Index (IHSG) crash between CNBC Indonesia and Bloomberg Technoz. Using Robert N. Entman's framing analysis model, which encompasses four dimensions (problem definition, causal interpretation, moral evaluation, and treatment recommendation), this study analyzed eight news articles published between January and April 2026. The findings reveal that CNBC Indonesia employs panic-driven framing characterized by hyperbolic and emotional diction such as "crash," "plummeted," and "blackout," tends to blame the government, and fails to provide concrete technical recommendations. In contrast, Bloomberg Technoz adopts data-driven framing based on fundamental and technical analysis, maintains a neutral and factual stance, and offers specific investment recommendations including price targets and risk management strategies. Despite their differences, both media acknowledge the severity of the crisis and implicitly criticize the government's communication transparency. This study contributes to extending Entman's framing model into the context of financial journalism in developing countries characterized by a massive retail investor base (26.12 million) with limited financial literacy.